ESTIMASI KETERSEDIAAN HARI KERJA UNTUK PENJADWALAN PROYEK KONSTRUKSI - Nurisra Nurisra; Nurul Malahayati; Mahmuddin Mahmuddin; Mubarak Mubarak (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2014)
Scheduling is one of the first steps undertaken by project owners and contractors before executing the project. In this planning, one of the factors that greatly affect the project schedule is weather, especially rainfall. High rainfall could potentially lead to disaster and construction projects carried out in an open environment is very sensitive to the influence of the weather. This study aimed to predict/forecast the pattern of rainy days that will generate working days calendar. The methodology of the study was conducted by collecting historical data of rainfall and the time schedule of the project. Forecasting of rainydays pattern was done with Markov chain theory and Monte Carlo simulation. Forecasting results show that the pattern of rainy days in February and December are the month with the lowest availability of working days. While March and Mayare the month that has the highest availability of working days. The level of availability of working days in a year is 88.8%, thus the forecasting results can be used for project scheduling. The forecasting programs will be integrated within the development of framework in forecasting rainy days of construction project scheduling models that effected by raining.